2014
DOI: 10.1002/anie.201404543
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Direct Hydrogenative Coupling of Nitroarenes To Synthesize Aromatic Azo Compounds

Abstract: The azo linkage is a prominent chemical motif which has found numerous applications in materials science, pharmaceuticals, and agrochemicals. Described herein is a sustainable heterogeneous-gold-catalyzed synthesis of azo arenes. Available nitroarenes are deoxygenated and linked selectively by the formation of N=N bonds using molecular H2 without any external additives. As a result of a unique and remarkable synergy between the metal and support, a facile surface-mediated condensation of nitroso and hydroxylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 53 publications
1
77
0
Order By: Relevance
“…Among the reported methods for the preparation of azo compounds, [85][86][87][88][89][90][91][92] this method has been found to be the most suitable. [93] We then focused our attention to study whether these azo compounds could be employed for the oxidative coupling of thiols to generate symmetrical disulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Among the reported methods for the preparation of azo compounds, [85][86][87][88][89][90][91][92] this method has been found to be the most suitable. [93] We then focused our attention to study whether these azo compounds could be employed for the oxidative coupling of thiols to generate symmetrical disulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Breakthrough in supported Au nanoparticles (NPs) provided new opportunities for the selective hydrogenation of nitroarenes. [17][18][19][20][21][22] Even so, it remains a grand challenge to realize commercialization because of the risk in supply, and volatile price. As a 3 response, intensive researches have been devoted to designing heterogeneous catalysts based on Earth-abundant metals, such as Fe, Co and Ni.…”
Section: Introductionmentioning
confidence: 99%
“…To further confirmt he reaction mechanism,P TAPw as directly synthesized by using the reductivec oupling reactiono fP T-2NO 2 with equivalent amounts of metal. [48] It has been demonstrated that Li ions can be used as reducing agents like H 2 to reduce NO 2 compounds to N=Nc ompounds during the electrochemical process. [29] Thus, Li metal is chosen as the reducing agent to chemically reduce PT-2 NO 2 ( Figure S25).…”
Section: Resultsmentioning
confidence: 99%